Landscape dynamics specific features of the river Volga estuarine natural systems particular long inundable territories - (:unkn) unknown (My University, 2019)
Multi-method landscape-ecological researches results on stationary parts in the river Volga delta, transformed to rank of natural sanctuary in the period of 1978-2016 are presented in this work. The main landscape dynamics tendencies are discovered, natural and anthropogenous factors of soil and vegetation cover are estimated for peculiar long inundable territories: water-soluble salts cationic- anionic analysis and their migration specific features and accumulation in dependence of the limited natural and anthropogenous factors changes for long inundable soil cover for forty years period; integrated effect of meteorological, hydrological, adaphic and anthropogenous factors cumulative changes on different years fluctuations and seral vegetational change for vegetation was revealed. Multi-year researches results show that the main factors, defining content and highly soluble salts radial migration in soils, also vegetation productivity and its species composition are hydrological regime (most of all – spring-summer floodings character) and territory climatic specific features. However, it is necessary to take into account local secondary effects influence, which can have an effective refracted impact on ambient background signals besides the main primary factors effect.
Специфические особенности ландшафтной динамики особо долгопоемных территорий устьевой природной системы р. Волги
В работе представлены результаты комплексных ландшафтно-экологических исследований на стационарных участках в дельте р. Волги, переведенных в ранг памятников природы, в период с 1978 по 2016 гг. Для особо долгопоемных территорий выявлены основные тенденции ландшафтной динамики, оценены природные и антропогенные факторы трансформации почвенно-растительного покрова: для почвенного покрова долгопоемных территорий за сорокалетний период проведен катионно-анионный анализ водорастворимых солей и особенностей их миграции и накопления в зависимости от изменений лимитирующих природных и антропогенных факторов; для растительности выявлено комплексное воздействие совокупных изменений метеорологических, гидрологических, эдафических и антропогенных факторов на разногодичные флуктуации и сукцессионные смены растительного покрова. Результаты многолетних исследований показывают, что основными факторами, определяющими содержание и радиальную миграцию легкорастворимых солей в почвах, а также продуктивность растительности и её видовой состав является гидрологический режим (прежде всего – характер весенне-летних половодий) и климатические особенности территории. Однако, помимо действия основных первичных факторов, необходимо учитывать и воздействие локальных вторичных, которые могут оказывать эффективное преломляющее воздействие на фоновые сигналы внешней среды.
Keywords: the river Volga delta; landscape structure; inundation; soil geochemistry; vegetation dynamics; deltoid ecosystems